Modulation of the ultradian human nasal cycle by sleep stage and body position - Richard E. Frye; Deborah F. Rosin; Adrian R. Morrison; Fidias E. Leon-Sarmiento; Richard L. Doty (Arquivos de Neuro-Psiquiatria)
ABSTRACT Objective: The nasal cycle, which is present in a significant number of people, is an ultradian side-to-side rhythm of nasal engorgement associated with cyclic autonomic activity. We studied the nasal cycle during REM/non-REM sleep stages and examined the potentially confounding influence of body position on lateralized nasal airflow. Methods: Left- and right-side nasal airflow was measured in six subjects during an eight-hour sleep period using nasal thermistors. Polysomnography was performed. Simultaneously, body positions were monitored using a video camera in conjunction with infrared lighting. Results: Significantly greater airflow occurred through the right nasal chamber (relative to the left) during periods of REM sleep than during periods of non-REM sleep (p<0.001). Both body position (p < 0.001) and sleep stage (p < 0.001) influenced nasal airflow lateralization. Conclusions: This study demonstrates that the lateralization of nasal airflow and sleep stage are related. Some types of asymmetrical somatosensory stimulation can alter this relationship.